IDENTIFIKASI JENIS MAKROALGA DI PANTAI LINAU, KABUPATEN KAUR, PROVINSI BENGKULU - Astini, Lita; Nur, Syarifudin; Yamadipo, Yusarwan; Astuti, Anggini Fuji (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Macroalgae is a biological resource that has great potential to be developed and is distributed in intertidal areas, consisting of various types with different characteristics. This research aims to determine the morphological characteristics of macroalgae types on Linau Beach, Kaur Regency, Bengkulu Province. The method used in this research is the observation and survey method, as well as the identification stage carried out in the intertidal zone of the beach. The results of research carried out at Linau Beach, Kaur Regency, Bengkulu Province, are that there are 14 species of macroalgae on sand, seagrass sand, sandstone, rock and coral substrates, consisting of 5 (five) species of the Chlorophyta (green algae) division, namely Ulva lactuca , Padina minor, Boergesenia forbesii, Chaetomorpha crassa, and Chaetomorpha antennina. The Phaeophyta (brown algae) division has 5 (five) species, namely Turbinaria ornata,, Sargassum polycystum, Sargassum cristaefolium, Sargassum paniculatum and Euchema denticulatum species E. and the Rhodophyta (red algae) division has 4 (four) species, namely Glacilaria salicornia, Achantophora spicifera, Khappaphycus alvarezii, and Gracilaria spp.